Effects of Using Composite Core on Relative Permeability Tests - Zaliran, Munirah (IRC, 2015)
This project entitled The Effects of Composite Core on relative Permeability Tests. Relative permeability test in this project is a Special Core Analysis in order to determine the relative permeability of the core plug. Relative permeability is the ratio of effective permeability of fluid at certain saturation to absolute permeability of fluid at total saturation. Composite core consist of several cores that put together during relative permeability test. It will focus on the usage of composite core during the tests to differentiate the value of relative permeability that obtain between single core and composite core. In addition, the arrangements for each single core in composite core also give effects on relative permeability tests. Unsteady state method will be used in order to determine the relative permeability value. The calculation adopted from Johnson, Bossler and Naumann (JBN) method. The experiment conducted in the laboratory by using Benchtop Permeability System. This project importance is to determine the relative permeability by using composite core because in the real reservoir, it is consists of different types of rock that have different value of relative permeability. Hence, the usage of composite core in relative permeability tests can describe the real situations of reservoir.